(untitled) (Encuentros, 2022)
Violence against children in Colombia is more evident if it is part of the armed conflict, where all forms of abuse against children and adolescents have been perpetrated, which is why this type of violence is relevant. analysis. In order to examine the situation of child abuse in the framework of the Colombian armed conflict, a qualitative / interpretive methodology will be applied to facilitate the exploration of the current data on this problem and to generate, in the end, Article.